Pengaruh Current Ratio (CR) Dan Net Profit Margin (NPM) Terhadap Harga Saham Melalui Earning Per Share (EPS) Sebagai Variabel Intervening Pada Perusahaan Pertambangan - Intafullaili, Bilgis Nisa'; Sriyono, Sriyono; Kumala Sari, Herlinda Maya (JURNAL MANAJEMEN MOTIVASI, 2025)
This study aims to analyze the impact of the Current Ratio (CR) and Net Profit Margin (NPM) on stock prices with Earnings Per Share (EPS)  as  an  intervening  variable  in  mining  companies.  This research employs a descriptive quantitative approach using panel data and purposive sampling techniques. The findings indicate that CR affects EPS but not significantly, while NPM has no significant impact  on  EPS.  Additionally,  CR  does  not  significantly  influence stock  prices,  whereas  NPM  and  EPS  have  significant  effects  on stock prices. However, EPS is not able to mediate the effect of CR and NPM on stock prices.